Three-factor model of the scale factor (SF) in the wear. Part 1 - Кузьменко, А.Г. (Problems of Tribology, 2015)
A method of constructing three factor analytic models tribology processes. In most cases, found that when other (pressure, friction path) conditions - the influence of the contact area of the linear or proportional.